SUPPORT-1 (Subjects Undergoing PCI and Perioperative Reperfusion Treatment): A Prospective, Randomized Trial of CMX-2043 in Patients Undergoing Elective Percutaneous Coronary Intervention - Tcheng, James E; Gibson, Michael; Krucoff, Mitchell W; Patel, Manesh R; Ajit, Mullasari; Hiremath, Jagdish; Ponde, Chandrashekhar; Ramsaran, Eddison; Clark, Geoffrey; Lader, Alan S; Beeuwkes, 3rd, Reinier (Journal of cardiovascular pharmacology, 2020)
The natural molecule α-lipoic acid has been shown to be partially cytoprotective through antioxidant and antiapoptotic mechanisms. To obtain an initial assessment of the safety and potential efficacy of a synthetic derivative, CMX-2043, in preventing ischemic complications of percutaneous coronary intervention (PCI) we conducted the Subjects Undergoing PCI and Perioperative Reperfusion Treatment (SUPPORT-1) trial, the first patient experience with this agent. SUPPORT-1 was a phase 2a, 6-center, international, placebo-controlled, randomized, double-blind trial. A total of 142 patients were randomized to receive a single intravenous bolus dose of drug or placebo administered 15-60 minutes before PCI. Cardiac biomarker assessments included serial measurements of creatine kinase myocardial band (CK-MB) at 6, 12, 18, and 24 hours after PCI and a single measurement of troponin T (TnT) at 24 hours. Peak concentrations of CK-MB and TnT were significantly reduced in the 2.4 mg/kg group compared with placebo (P = 0.05 and 0.03, respectively). No subject administered 2.4 mg/kg of CMX-2043 had an increase of CK-MB to ≥3X upper limit of normal versus 16% for placebo (P = 0.02); 16% of the 2.4-mg/kg dose group developed an elevation of TnT to ≥3X upper limit of normal versus 39% in the placebo group (P = 0.05). No drug-related serious adverse events were observed in any group. These data suggest that CMX-2043 may reduce PCI periprocedural myonecrosis and support further clinical evaluation of this novel agent for its potential cytoprotective effects.